ALGORITHMS OF THE AUTOMATIC DIGITAL ANALYSIS OF VEGETABLE SEEDS QUALITY - F. В. Musaev; М. S. Antoshkina; A. V. Soldatenko; S. L. Beletsky; N. N. Potrakhov (Овощи России, 2018)
The seed fund is considered as a basis of food independence of the country and seed certification in many developed countries, including the Russian Federation, is care of the state. Seed farming of vegetable cultures in our country is complicated by adverse soil-climatic conditions of the majority of regions. The quality of the made seeds which does not conform to requirements of the modern agriculture providing uses of the homogeneous seeds with high field viability remains the main problem of branch. The modern level of development of scientific knowledge provides application of instrumental methods of the analysis of quality of the seeds differing in high informational content, speed and ease of execution. We developed and approved a method X-ray analysis of quality of vegetable seeds. Now programming, automation of this method is conducted. The way of the digital analysis of x-ray images in the automatic mode comes to replacement of earlier applied visual analysis of radiographs of seeds. The modernized hardware and software system is developed and approved, the program algorithm consisting of several stages is developed. There is a completion and approbation of the new software for the automatic analysis of graphic files of X-ray image of seeds of vegetable cultures under the name "Sortsemkontrol-1.0". Development and deployment of a method of the automatic analysis of x-ray images of vegetable seeds is essential to accelerate process, will increase its informational content and will allow to get rid of subjectivity, connected by the visual analysis of radiographs.